The Effect of Dielectric Barrier Discharge Plasma on Lactobacillus acidophilus: An In Vitro Study: Effect of DBD Plasma on Lactobacillus acidophilus - Shahhosseini, Ghazaleh; Alirezaei, Somayeh; Alaee, Arezoo; Fattahi, Mahsa (Journal of Lasers in Medical Sciences, 2025)
Introduction: Dental caries remains a prevalent oral health issue worldwide, with Lactobacillus acidophilus playing a significant role in its progression. While traditional antimicrobial agents like chlorhexidine are effective, the increasing concern of antimicrobial resistance has spurred interest in alternative approaches. Dielectric barrier discharge (DBD) plasma, a form of cold atmospheric plasma (CAP), has shown promise in various biomedical applications, including dentistry. This in vitro study aims to determine the effect of DBD plasma radiation on the amount of L. acidophilus bacteria. Methods: Lactobacillus acidophilus (ATCC 43121) cultures were subjected to DBD plasma reatment for 30, 90, 120, and 150 seconds. A positive control group was treated with 2% chlorhexidine, and a negative control received no treatment. Bacterial viability was assessed using colony-forming unit (CFU) counts. One-way ANOVA and Tukey’s HSD test were used for statistical analysis. P values less than 0.05 were considered significant. Results: The 30-second DBD plasma treatment significantly reduced L. acidophilus populations compared to the negative control (32.9% reduction, P<0.001). However, longer exposure times (90, 120, and 150 seconds) showed diminished antibacterial effects. The 2% chlorhexidine treatment demonstrated the highest antibacterial efficacy (54.8% reduction, P<0.001 compared to all other groups). Conclusion: It seems that short-duration DBD plasma treatment (30 seconds) effectively reduced L. acidophilus populations, although not as efficiently as chlorhexidine. Interestingly, prolonged plasma exposure did not enhance antibacterial effects, suggesting a potential adaptive response of bacteria to extended plasma treatment. These findings highlight the promise of DBD plasma as a novel approach to dental caries prevention while emphasizing the need for optimized treatment parameters.